Hubungan Antara Persepsi dan Tingkat Partisipasi Petani Padi Sawah dengan Tingkat Keberhasilan Program PHT - Sandi, Luki; Virianita, Ratri (Departemen Sains Komunikasi dan Pengembangan Masyarakat, Fakultas Ekologi Manusia, IPB, 2019)
Pengendalian Hama Terpadu (PHT)is an attempt by the government to food self-sufficiency and improve the welfare of the farmer. Perception and participation is an important aspect that determines the success of PHT Program. This researchaims: (1) to describe the perception of field paddy farmer toward PHT Program inKarangwangi Village, (2) to describe the participation level of field paddy farmer in PHT Program in Karangwangi Village, (3) to describe the implementation andsuccess rate of PHT Program in Karangwangi Village, (4) to analyze the relationship between perception and participation level of field paddy farmerin PHT Program in Karangwangi Village, and (5) to analyze the relationship between participation level of field paddy farmer and success rate of PHT Program inKarangwangi Village. The results of this study were: (1) the perception was in the neutral category, (2) the level of participation in the medium category, (3) PHT Program success rate was in the medium category, (4) there is relationship between perception and participation level (rs: 0,888; p < 0,01), and (5)there is a relationship between participation level and PHT Program success rate (rs: 0,869; p < 0,01).Keywords: participation, perception, PHTABSTRAKPengendalian Hama Terpadu (PHT) is an attempt by the government to food self-sufficiency and improve the welfare of the farmer. Perception and participation is an important aspect that determines the success of PHT Program. This research aims to analyze the relationship between perception with participation level of field paddy farmer in PHT Program in Karangwangi Village and to analyze the relationship between participation level of field paddy farmer with success rate of PHT Program in Karangwangi Village. This research are use survey metode with quantitative approach supported by qualitative data. For relationship analysis in this research used statistic test of rank spearman. Based on data result, the perception was in the neutral category. The level of participation in the medium category. PHT Program success rate was in the medium category. Statistic test result is explain there is relationship between perception and participation level (rs: 0,888; p < 0,01) and there is a relationship between participation level and PHT Program success rate (rs: 0,869; p < 0,01).Keyword: participation, perception, PHT